Radial-Probe Endobronchial Ultrasound as Part of Different Navigational Bronchoscopy Modalities in Combination with Cryobiopsy Could Be More than a Confirmation Tool: A Case Series - Nevenka Piskac Zivkovic; Maja Karaman Ilic; Suncana Divosevic; Hrvoje Feljan; Igor Nikolic; Zrinka Juros; Ana-Marija Sola; Sven Seiwerth; Dragan Schwarz; Ivica Mazuranic (Diagnostics)
Background: As part of different navigational bronchoscopy (NVB) modalities, radial-probe endobronchial ultrasound (rEBUS) is used to confirm the peribronchial localization of peripheral pulmonary nodules (PPNs) immediately before collecting samples for histopathological analysis. Methods: This retrospective case series study presents the results of en bloc cryobiopsy of PPNs using a flexible 1.1-mm cryoprobe with different NVB modalities. For PPNs classified as adjacent or eccentric lesions by rEBUS (ES-rEBUS), the cryoprobe’s position was adjusted by 90–180° in relation to the ultrasound image of the lesion during the first and second biopsies. Results: All patients with a final histopathologically confirmed diagnosis of PPNs had positive rEBUS findings, regardless of the navigation modality, eccentric (18/42 patients, 43%) and concentric (24/42 patients, 57%) rEBUS view. In 5 out of 6 patients without a histopathological diagnosis, PPNs were not visualized by radial ultrasound. In the (ES-rEBUS) group of patients, 4 out of 18 had fewer than three biopsy samples collected per procedure, which means only an adjusted probe position has been applied, although diagnostic outcomes were achieved. Common Terminology Criteria for Adverse Events (CTCAE) grade 2 complications were reported in 10.4% of the patients, and grade 3 complications in 2% of the patients. Conclusions: Confirming the localization of nodules by rEBUS and properly adjusting the cryoprobe immediately before cryobiopsy of PPNs resulted in a diagnostic yield meeting the literature standards.